Recepcija Goethejevega Fausta pri Slovencih - Bernik, France (Primerjalna književnost, 1999)
The reception of Goethe's Faustus in Slovenia. The paper describes the reception in Slovenia of one of the most important plays of German and world literature, and establishes how Goethe's Faustus has been accepted by expert readers, namely translators, literary authors, critics and literary scientists of various orientations. The author does not stop at citations of Faustus or passing comments on it in the press, but also takes into account holistic, more ambitiously set out views on this central work mentioned by Slovene journalists when translations of the work, either as a whole or in excerpts, were published, or on the writer's anniversaries.
Keywords: Goethe, Johann Wolfgang von, 1749-1832; nemška književnost; German-language literature; Goethe, Johann Wolfgang von: Faust; literarne študije; prevodi